ANALYSIS OF BPD BALI MOBILE USAGE ON CUSTOMER INTEREST IN TRANSACTIONS - Dewi, Kadek Safira Permata; Wirsa, I Nengah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Competition in the financial business is getting tougher in local and international markets. Banks that strive to grow and achieve competitive advantage must be able to provide clients with better services than their competitors. Customer interest in transactions is a success factor for a bank in improving and developing the quality of its services. The quality of customer service is very important for companies to be managed properly in order to continue to gain customer trust and satisfaction. PT Bank Pembangunan Daerah Bali must provide the best service supported by adequate facilities and infrastructure. One form of facilities and infrastructure that can improve the quality of service of a service provider (bank) is to provide services through electronic media or e-banking. Problems with the e-banking application of PT Bank Pembangunan Daerah Bali have weaknesses that reduce customer interest in using this application. This research aims to be used as evaluation material by Bank BPD Bali Province in improving and improving service performance through electronic media.